Listening at the Edge: Homage and Ohmage in Don McKay and Ken Babstock - Mason, Travis V. (Studies in Canadian Literature, 2008)
Don McKay’s observant lyric and prose writings combine homage and "ohmage," which invite ecological readings, and his editorial engagement with many Canadian poets incites public awareness of a thriving poetry, a sort of verse ecology interested in public listening. In congruence with Bruno Latour’s view of the interconnectedness of the two spheres, McKay enacts connections in his poetry between understanding ecosystems and reviving public life. He puts these connections into action by mentoring and editing the work of other writers, and the influence of his poetics is particularly noticeable in Ken Babstock’s first collection, Mean (1999). The ecopoetical content of McKay’s poems combines with certain linguistic tropes (what Donna Haraway calls "metaplasm") to construct a community, if not an ecology, of listening that has the potential to inflect the way readers hear and think about poetry.